Ilmu Maqashid Dalam Tradisi Pemikiran Ulama Ushul - Fadila Sidiq Permana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
In religion, there are universal values that can not be hit by nash-nash that are particular. This means that religious teachings that are more universal must take precedence over laws of a particular nature. In understanding the universal religious teachings the scholars have formulated five basic benefits in religion. These five things include the benefit of religion, soul, reason, offspring, and wealth. As for exploring specific particular evidence, we need to understand the concept of understanding the reason ('illat) of teaching. This requires a search of the books by ushul scholars that discuss many things related to maqashid al-sharia, fiqh rules, and the search process 'illat. This is done so that the texts of the Qur'an and Sunnah are more alive, dynamic, and flexible to answer the times.